2023
DOI: 10.1021/acs.analchem.2c05689
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Affinity-Based Chemical Proteomics Method to In Situ Capture Amorphous Aggregated Proteome and Profile Its Heterogeneity in Stressed Cells

Abstract: Stress induced amorphous proteome aggregation is a hallmark for diseased cells, with the proteomic composition intimately associated with disease pathogenicity. Due to its particularly dynamic, reversible, and dissociable nature, as well as lack of specific recognition anchor, it is difficult to capture aggregated proteins in situ. In this work, we develop a chemical proteomics method (AggLink) to capture amorphous aggregated proteins in live stressed cells and identify the proteomic contents using LC-MS/MS. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Hong 22–24 and Hatters 25–27 proposed using maleimides to label unfolding proteins, while Zhang 28–31 used chemical labelling techniques (Halo Tag or SNAP-tap) to visualize and quantify protein aggregates in living cells through biorthogonal reactions. Liu group 32–39 developed a series of fluorescence probes based on changes in the microenvironment. However, limited studies use these probes in clinical samples or to compare protein aggregates in tumour tissues to those in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hong 22–24 and Hatters 25–27 proposed using maleimides to label unfolding proteins, while Zhang 28–31 used chemical labelling techniques (Halo Tag or SNAP-tap) to visualize and quantify protein aggregates in living cells through biorthogonal reactions. Liu group 32–39 developed a series of fluorescence probes based on changes in the microenvironment. However, limited studies use these probes in clinical samples or to compare protein aggregates in tumour tissues to those in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, its poor permeability limits its application to aggresome detection in fixed cells. Hong and Hatters’ teams pioneered in developing unfolded proteome sensors applicable in live cells using covalent maleimide chemistry to capture exposed cysteine residues upon protein unfolding. Zhang’s group reported environment-sensitive fluorophores that detect soluble oligomers and insoluble aggregates in live cells using genetically encoded HaloTag and SNAP-tag. Our group and others previously reported that fluorescent protein chromophores can be used to detect amorphous proteome in live cells. However, nearly all of these sensors to detect intracellular misfolded and amorphous aggregated proteome are limited to cell samples. Particularly, the binding mechanism and rational design rationale remain elusive, impeding further optimization and development of new sensors to detect proteome aggregation in more complex biological samples, such as tissue samples or ultimately live animal models.…”
Section: Introductionmentioning
confidence: 99%
“…24,35–39 Meanwhile, chemical proteomics tools were developed to resolve the composition of aggregated proteome in the cell. 40,41 However, most of the reported sensors are limited to their applications in cultured cell lines. Proteome aggregation upon cellular stresses may become an early diagnosis indicator prior to the diseased state if it can be reliably reported using clinical patient-derived samples.…”
Section: Introductionmentioning
confidence: 99%